THE EFFECT OF FINANCIAL AND NON-FINANCIAL PERFORMANCE ON REGIONAL COMPETITIVENESS OF BUNGO DISTRICT WITH CAPITAL EXPENDITURE AND BUDGET GOVERNANCE AS INTERVENING - Herawati; Syamsurijal Tan; Sri Rahayu; Syahmardi Yacob (Bajang Institute, 2021)
This study aims to determine the effect of financial and non-financial performance, capital expenditure, budget management on regional competitiveness. Second, this study also determines the impact of financial and non-financial performance on regional competitiveness through capital expenditures and budget management in the Bungo Regency. Primary data were collected through direct interviews with respondents with predetermined criteria and processed using Structural Equation Model analysis with PLS. The results study found only financial and non-financial performance and budget management had a significant effect on regional competitiveness, while capital expenditure had no effect. This study also found that financial and non-financial performance affects regional competitiveness through budget management, but it had no effect if capital expenditures were intervening.